IMPROVING STUDENTS’ VOCABULARY ACHIEVEMENT BY USING CROSSWORD PUZZLE - Siti Rina Anugerah and Sortha Silitonga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study was conducted as an attempt to improve students’ vocabulary achievement on Grade VIII by applying crossword puzzle. It was conducting by using Classroom Action Research. The subject was 38 students of grade VIII of SMPN 35 Medan and was conducted in two cycles. It is consisted of two kinds of instruments namely quantitative and qualitative data. For quantitative data was used vocabulary test which was teachers’ made, and for qualitative data were used diary notes and interview sheets. Based on the data and data analysis, it can be seen that there was an improving of students’ score in cycle I and cycle II, which can be approved from the mean of each test, that were 65.90, 73.92, and 81,25. After applied the crossword puzzle, it can be seen that that vocabulary achievement of the students in SMPN 35 Medan was increase. The research result showed that the application of crossword puzzle in teaching English especially in vocabulary is an effective way to improve the students’ achievement.